(untitled) (CIPEEX, 2022)
PLATELETS ARE ANUCLEATED CELL FRAGMENTS OBTAINED THROUGH THE PROCESS OF PROLIFERATION AND DIFFERENTIATION OF MEGAKARYOCYTES, A PROCESS CALLED MEGAKARYOCYTOSIS. THESE STRUCTURES PLAY AN IMPORTANT ROLE IN HEMOSTASIS DUE TO THEIR ADHESION AND AGGREGATION FUNCTIONS FOR THE FORMATION OF PLATELET BUFFER AT THE VASCULAR ENDOTHELIAL LESION SITE. THE DETERMINATION OF THE NUMBER OF PLATELETS IN THE BLOOD CIRCULATION CAN BE PERFORMED EITHER BY CONVENTIONAL METHODS OR BY AUTOMATIC HEMATOLOGICAL COUNTERS, THE LATTER BEING A METHOD THAT PROVIDES PLATELET INDEX VALUES, PARAMETERS THAT ARE LITTLE USED IN CLINICAL PRACTICE. AMONG THE MAIN PLATELET INDEXES IS THE PLATELET DISTRIBUTION WIDTH (PDW) WHICH ANALYZES THE PLATELET DISTRIBUTION AMPLITUDE BASED ON SIZE, AND A PLATELET INDEX THAT REFLECTS HOW UNIFORM THE PLATELET SIZE IS. DECREASED PLATELET (PLT) IS THE DETERMINATION OF THE NUMBER OF PLATELETS PER MM3 OF BLOOD, USUALLY THIS PLATELET INDEX IS BETWEEN 150,000 TO 400,000 PLATELETS / MM3 OF BLOOD. PLATELET (PCT) CORRESPONDS TO THE TOTAL VOLUME OF PLATELETS IN A GIVEN VOLUME OF BLOOD AND IS DIRECTLY RELATED TO THE PLATELET COUNT AND THE MEAN PLATELET VOLUME (MPV), WHICH IS CONSIDERED A MARKER INDEX OF PLATELET FUNCTION. THE OBJECTIVE OF THE PRESENT STUDY WAS TO INVESTIGATE THE CLINICAL INDICATIONS OF PLATELET INDICES. FOR THE ACCOMPLISHMENT OF THE STUDY 10 ARTICLES WERE PRESENTED THAT APPROACHED THE PROPOSED THEME. AFTER READING THE ARTICLES, WE SELECTED THE MAIN CLINICAL INDICATIONS OF THE PLATELET INDEXES REPORTED BY THE RESEARCHERS. HEMOSTASIS IS DEPENDENT ON THE GOOD FUNCTIONING OF PLATELETS AND PLASMA FACTORS. DISEASES CAUSED BY THE DISORDER OF THESE COMPONENTS, ESPECIALLY THOSE INVOLVING PLATELETS ARE RESPONSIBLE FOR THE THROMBOCYTOPENIA AND THROMBOCYTOPENIA, THE INCREASE AND THE DECREASE OF THE AMOUNT OF PLATELETS IN THE BLOOD, RESPECTIVELY. THESE PICTURES MAY INTERFERE WITH THE VALUES €‹€‹OF THE PLATELET INDEXES AND INDICATE HEMATOLOGICAL PATHOLOGIES OF THE WHITE SERIES. THE VPM HAS ACQUIRED GREAT IMPORTANCE IN THE CLINICAL PATHOLOGY, BEING USED TO DETERMINE THE MORBIDITY AND MORTALITY IN SEVERAL NOSOLOGICAL ENTITIES OF DIVERSE PATHOPHYSIOLOGIES (INFECTIONS, CARDIOVASCULAR DISEASES, METABOLIC DISORDERS) . IN ADDITION, IT WAS DEMONSTRATED THAT THE INCREASE IN MPV WAS ASSOCIATED WITH A POOR PROGNOSIS IN PATIENTS WITH DIABETES MELLITUS, SEPSIS, PULMONARY EMBOLISM, SMOKING AND IMMUNO-INFLAMMATORY DISEASES. PDW REPRESENTS PLATELET MASS AND MAY BE DECREASING IN MARKED THROMBOPENIA, SITUATIONS IN WHICH THE BODY CAN NOT COMPENSATE FOR PLATELET MASS. INCREASED PLT MAY INDICATE IDIOPATHIC MYELOID METAPLASIA, CHRONIC MYELOGENOUS LEUKEMIA, RHEUMATOID ARTHRITIS, ENTERITIS, TUBERCULOSIS, SARCOIDOSIS, ACUTE INFECTION, HEMORRHAGE, AND IRON DEFICIENCY. DECREASED VALUES €‹€‹MAY INDICATE RUBELLA, CYTOMEGALOVIRUS, EPSTEIN-BARR VIRUS, HIV, ALCOHOLISM, HYPERSENSITIVITY TO HEPARIN, THIAZIDE DIURETICS, SPIRONOLACTONE, ESTROGENS, CHEMOTHERAPEUTICS AND IMMUNOSUPPRESSIVE DRUGS. FROM THE STUDY, IT CAN BE CONCLUDED THAT ALTHOUGH THE PLATELET INDEXES ARE NOT VERY USED IN CLINICAL PRACTICE, THEY CAN BE DETERMINANT TOOLS IN THE STUDY OF HEMATOLOGICAL OR NON-HEMATOLOGICAL DISEASES, MAKING MORE COMPLEX AND IN-DEPTH STUDIES ON THE SUBJECT WITH THE OBJECTIVE OF DESCRIBING THE MAIN CLINICAL INDICATIONS OF PLATELET INDEXES.